Improving Weather Display Interpretation: A Training Solution. (December 2020) - Kleber, John; McSorley, Jacqueline; King, Jayde; Blickensderfer, Beth
Visual flight rules (VFR) operations into instrument meteorological conditions (IMC), is one of the deadliest causes of weather-related accidents in the General Aviation (GA) community. Current weather training for GA pilots is inadequate. This paper describes the design and development of three weather training modules and provides research-based recommendations for the development of future training modules for aviation weather. Recommendations include incorporating simulation-based training, utilizing available materials, prioritizing accessibility, accounting for changing technology, maintaining high cognitive fidelity, and using a multidisciplinary team approach.